Empowerment Model to Enhance Food Self-Sufficiency at Mushroom Industry Center - Suranto Suranto; Adcharina Pratiwi (Postgraduate, University of Mataram, 2023)
This research formulates a good and proper empowerment model for mushroom farmer groups in order to increase the self-sufficiency of mushroom food independence. The model developed through empowering mushroom farmers by making baglogs, F0 and F1, to the sale of fresh and processed mushroom products, both online and offline based among. Data collection is used through observation, interviews, questionnaires, documentation and surveys. The analysis method with project-based learning works directly on empowerment activities (mentoring, counseling, direct action services) in order to increase food self-sufficiency from upstream to downstream (making F0 seeds, F1 baglogs to production). Model development with path analysis is to build a among-based empowerment model formulation. The among-based empowerment strategy is developed and implemented through independent learning that places participants as objects and subjects. Participants in the empowerment of mushroom farmers, prioritize family values, physical and mental independence. The data analysis method uses the concept of a hypothetical model and analyzes the behavioral trends of mentoring participants and the results of the formulation of among-based empowerment are able to improve the mushroom food independence